Seismicity in the equatorial margin of Brazil reactivates the Precambrian basement fabric. (March 2021) - Ramos, Gilsijane V.; de Castro, David L.; Bezerra, Francisco H.R.; Ferreira, Joaquim Mendes; do Nascimento, Aderson F.; de Oliveira, Paulo H.S.; Nogueira, Francisco C.C.
Abstract: The continental margin of Brazil in intraplate South America exhibits a seismicity rate 70% higher than the average stable continental regions. This margin encompasses Northeastern Brazil, where most of the seismicity and active faults concentrate along the coast. The current study presents an integration of high-resolution aeromagnetic, seismological, and geological data to investigate the relationship between the seismicity and basement fabric in two areas in the northern part of the Precambrian Borborema Province. Our investigation indicates a relation between the metamorphic basement foliation and two seismogenic faults. In the first area adjacent to the Transbrasiliano Lineament, the largest continental suture zone in the South American platform, the magnetic anomaly patterns indicate that the regional basement grain and structural elements are E-W-oriented, which coincides with the strike of the E-W-striking, strike-slip Riacho Fundo Seismogenic Fault. In the second area, the magnetic anomaly patterns also coincide with the NE-SW-striking, strike-slip Samambaia Fault, and a swarm of chalcedony-quartz veins. Euler deconvolution used to estimate the source depth of the magnetic anomalies indicates that the faults in both cases could be longer and deeper than segments illuminated by the present-day seismicity. Although these findings are difficult to use as predictive tools, they indicate that the basement fabric could be reactivated by seismicity in continental interiors, as previously discussed in several cases in Brazil. Highlights: We investigate basement fabric reactivation using airborne magnetic data. The magnetic anomalies mark the Precambrian fabric in the seismogenic crust. Seismicity reactivates the Precambrian fabric along the Equatorial margin of Brazil. The seismogenic faults show magnetic signatures that match the hypocenter locations.